The Influence of Islamic Teachers on the Ethichs of Islamic Communication in Vocational High School in Deliserdang Regency - Datok Bondaharo; Syukur Kholil; Lahmuddin Lubis (Britain International for Academic Research (BIAR) Publisher, 2020)
the perspective of Islam as written by Muslimah from the An-Nadwah Kuala Tungkal Islamic College of Religion (STAI), the communication meant by Islamic communication is communication that is morally al-karimah or ethical. This aim of paper intends to raise the discourse regarding the ethics of communication that occur in the world of Education, especially what happens to students who are in Vocational High School I Percut Sei District, Deli Serdang Regency. This study uses a quantitative approach. The population of this research is the students of Vocational High School I Percut Sei District Tuan Deli Serdang Regency. the total population of the three class levels is 2174 people. The results show that Peer communication to public vocational high school students 1 Percut Sei Tuan Deli serdang has a significant effect on students' Islamic communication ethics. This influence is shown by the contribution of peer communication by 0.218 units to the ethics of Islamic communication of students. Peer communication has a positive effect on students' Islamic communication ethics. The better the peer communication with students, the better the ethics of student Islamic communication. Family communication, communication of Islamic religious education teachers and peer communication together have a significant effect on the ethics of Islamic communication of students. The influence is 50.9%. This means ethics.